Chrestenson-Levy system and step scaling functions - Ю.А. Фарков (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2020)
Using the Chrestenson-Levy system and the modified Cohen condition, step scaling functions are constructed that generate multiresolution analyzes in L2 (R+) . Analogies with orthogonal wavelet constructions and Parseval frames for Vilenkin groups are discussed.